Tensor Network Contractions : Methods and Applications to Quantum Many-Body Systems /: Methods and Applications to Quantum Many-Body Systems. (2020) - Ran, Shi-Ju; Tirrito, Emanuele; Peng, Cheng; Chen, Xi; Tagliacozzo, Luca; Su, Gang; Lewenstein, Maciej
No abstract available